PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN PERKEMBANGAN KOGNITIF DALAM MENGENAL LAMBANG BILANGAN - Desy Pratiwi Handaryani, Ni Md; Pudjawan, I Ketut (Universitas Pendidikan Ganesha, 2018)
This research is a classroom action research which aims to determine the improvement of cognitive development in recognizing the number symbol after applying the make a match learning model to the children of A1 TK Kartika VII-3 Singaraja group. This research is classroom action research (CAR) which is carried out in two action cycles. The subjects of this study were students of A1 group TK Kartika VII-3 Singaraja in 2018/2019 Academic Year which consisted of 18 students, consisting of 8 girls and 10 boys. The analytical method used is descriptive statistical analysis method and quantitative descriptive analysis method. The results of data analysis in this study indicate that there is an increase in the average percentage of cognitive development in recognizing the symbol of numbers in children in group A1 of 15.25%. This can be seen from the increase in the average percentage of cognitive development in recognizing the symbol of child numbers in the first cycle of 65.25% with the criteria being medium to 80.50% in cycle II with high criteria. Thus, it can be concluded that the application of the make a match learning model can improve cognitive development in recognizing the symbolic number of children in Group A1 TK Kartika VII-3 Singaraja Academic Year Â 2018/2019Â Keywords: Make a match, Cognitive Development, Number Symbols